Exploring Consumer Perceptions on Meat Alternative Products - Ndenze, Faith (The IIE, 2022)
Sustainability of the environment as well as the health and nutrition of consumers are some of the main global concerns right now. The aim of this research is to explore how vegetarian and vegan consumers perceive the consumption of meat alternative products in Cape Town. This knowledge will assist the researcher to determine whether vegetarian and vegan consumers believe that the consumption of meat alternative products has any impact on the sustainability of the environment and the health and nutrition of consumers. A semi-structured interview schedule that was developed from the literature review, probed whether the consumption of meat alternative products had any impact on the health of consumers and the sustainability of the environment. The interview schedule also probed the role played by the brands that manufacture meat alternative products in creating awareness. In-depth interviews were conducted with six participants, five of which are vegan with one being vegetarian. In this study, the researcher investigates sustainability of the environment and nutrition as the major cause of moving towards meat alternative products. The researcher also investigated health concerns as a reason to move towards meat alternative products, attitudes towards meat alternative products, meat alternative product brands as well as consumer willingness to pay for meat alternative products. The investigation discovered that consumers that follow a vegan and vegetarian diet are aware of meat alternative products. The study however discovered that consumers following a vegan and vegetarian diet prefer to consume meat alternative products sparingly as they believe they are highly processed and are not as nutritious as plant based proteins such as legumes.
Keywords: Environment; Consumer behaviour; Health; Diets